The Impact of EU Enlargement on European Border Regions - Annekatrin Niebuhr (European Regional Science Association (ERSA), 2005)
EU enlargement is supposed to entail profound impact on the location of economic activities in Europe. Although there is concern about the implications of enlargement for regional disparities in the EU, corresponding empirical results are still rare. The objective of this analysis is to provide empirical evidence on enlargement effects with a special focus on border regions in the EU27 since they are likely to play a critical role within the spatial dynamics initiated by integration. Departing from a three-region economic geography model we investigate whether changes in market access released by integration result in above-average integration benefits in internal border regions.
Keywords: 330